Antimicrobial activity of natural products against Helicobacter pylori (Revista Venezolana de Salud Pública, 2018)
Since its discovery and identification in gastric tissue by Marshall and Warren in 1983, our knowledge about the effects of Helicobacter pylori infection has grown considerably. Its role in the multifactorial pathology of peptic ulcer disease (gastroduodenal ulcer disease), gastric adenocarcinoma, is now widely accepted. Currently, numerous antibiotic-based therapies are available. However, these therapies have several problems, including the appearance of resistance to the antibiotics used and associated adverse effects, the risk of re-infection and the high cost of treatment. This paper summarizes and analyzes the most important recent studies of plants with anti H. pylori activity. Plants species are presented as a very diverse source of bactericidal compounds, as well as for the development of new therapies for H. pylori control.
Keywords: Helicobacter pylori; natural products; antimicrobial activity; plant-derived agents